The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1126/science.1254082
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Specific and nonhepatotoxic degradation of nuclear hepatitis B virus cccDNA”

Abstract: ) report that the hepatitis B virus (HBV) transcriptional template, a long-lived covalently closed circular DNA (cccDNA) molecule, is degraded noncytolytically by agents that up-regulate APOBEC3A and 3B. If these results can be independently confirmed, they would represent a critical first step toward development of a cure for the 400 million patients who are chronically infected by HBV. V iral clearance during acute hepatitis B virus (HBV) infection is mediated by CD8-positive cytotoxic T lymphocytes (CTL) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…While various steps of the replication cycle might be affected,132 a recent study137 suggested that very-high-dose interferon-α, or more potently activation of the lymphotoxin-β receptor, could directly target cccDNA integrity via APOBEC3A and 3B-mediated deamination of the (-)-strand and subsequent degradation. Though some aspects are controversial,138 139 the worthiness of activating innate responses is underlined by promising preclinical results with the Toll-like receptor 7 agonist GS-9620 140…”
Section: Ridding the Liver Of Cccdnamentioning
confidence: 99%
“…While various steps of the replication cycle might be affected,132 a recent study137 suggested that very-high-dose interferon-α, or more potently activation of the lymphotoxin-β receptor, could directly target cccDNA integrity via APOBEC3A and 3B-mediated deamination of the (-)-strand and subsequent degradation. Though some aspects are controversial,138 139 the worthiness of activating innate responses is underlined by promising preclinical results with the Toll-like receptor 7 agonist GS-9620 140…”
Section: Ridding the Liver Of Cccdnamentioning
confidence: 99%
“…Moreover, both of these small DNA viruses specifically upregulate A3B at the transcriptional level (Mori et al, 2017; Starrett et al, 2017; Verhalen et al, 2016; Vieira et al, 2014). Second, A3B knockdown in liver-derived HepG2 cells results in elevated levels of HBV circular DNA replication intermediates suggesting A3B may have a role in suppressing virus replication (Lucifora et al, 2014), however this result has been debated (Chisari et al, 2014; Ding and Robek, 2014; Meier et al, 2017; Shlomai and Rice, 2014; Xia et al, 2014). Disagreement also exists regarding HBV infection rates in individuals lacking the entire A3B gene due to a common deletion allele [higher: (Prasetyo et al, 2015); unchanged: (Ezzikouri et al, 2013)].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also proposed the use of LTbR agonists as a potential anti-HBV therapy, likely in combination with other antiviral strategies. While the results are intriguing, some important technical concerns have been raised, 14,15 and there are other essential questions that remain to be addressed. First, as multiple APOBEC3 family members have now been shown to target a number of different HBV DNA replication forms, it will be important to understand the specificity and nature of these interactions.…”
Section: Commentmentioning
confidence: 99%